TikTok for Vocabulary Learning: A Comparative Study of Perceptions Among Basic and Intermediate Proficiency EFL Students - Syarifah, Nur Laila; Sholah, Hanif Maulaniam (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study investigates students’ perceptions of the TikTok platform as a medium for enhancing English vocabulary learning at SMP Annida Krebetsenggrong Malang. The rapid growth of social media, particularly TikTok, has created new opportunities for integrating technology into language education. However, the effectiveness of TikTok for vocabulary development among learners with different proficiency levels remains underexplored. Therefore, this study aims to examine how students from basic and intermediate proficiency perceive the use of TikTok for vocabulary learning and to identify the challenges they encounter while using it as a learning medium. This study employed a qualitative descriptive. Five students were selected through purposeful sampling, consisting of three elementary-level and two intermediate-level learners who actively used TikTok for English learning. Data were collected through written proficiency tests and structured interviews. The results revealed that both basic and intermediate students generally perceived TikTok as an enjoyable and effective platform for learning new vocabulary. basic-level students emphasized that TikTok made vocabulary learning more interesting, creative, and easy to understand through short, visual, and engaging content. Intermediate students acknowledged similar benefits but also noted limitations, such as distractions from non-educational content and the short duration of videos, which hindered deeper understanding.